The Effect of Digital Media-Based Nutrition Education on Animal-Based Food Feeding Behavior Among Parents of Toddlers: A Quasi-Experimental Study - Wibowo, Daniel Akbar; Zen, Dini Nurbaeti; Ginanjar, Yoga (Chakra Brahmanda Lentera Institute, 2025)
Background: Low consumption of animal source foods (ASF) among children under five years children in Indonesia contributes to the high prevalence of stunting. Digital media–based nutrition education can potentially improve parental ASF feeding behavior. However, empirical evidence on its effectiveness in semi-urban and rural settings, particularly studies directly measuring parental behavioral change, remains limited. This study aimed to analyze the effect of digital media–based nutrition education on parental ASF feeding behavior among under-five children. Methods: This quasi-experimental one-group pretest–posttest study involved 150 parents of under-five children in Sukadana Village, Ciamis Regency, West Java, Indonesia, selected through stratified purposive sampling by hamlet. Inclusion criteria: parents with children <5 years old, having smartphone access, willingness to participate in the intervention, and provision of written informed consent. Exclusion criteria: incomplete pretest or posttest questionnaire data. The intervention consisted of a ±10-minute educational video on the importance of ASF, its sources, safe preparation, and tips to increase consumption, validated by nutrition experts. Feeding behavior was measured using a structured questionnaire (20 items; 3-point Likert scale; Cronbach’s alpha = 0.82). Data were analyzed using paired sample t-tests and effect size calculation (Cohen’s d) with 95% confidence intervals (CI) in SPSS v26. Results: Digital media–based nutrition education significantly improved parental ASF feeding behavior (p < 0.001), with a large effect size (Cohen’s d = 0.91; 95% CI: 0.69–1.12). The proportion of good behavior increased from 28.0% to 84.0%, while fair and poor behaviors decreased from 43.3% to 12.7% and from 28.7% to 3.3%, respectively. Conclusion: Digital media–based nutrition education is efficacious in improving parental ASF feeding behavior in semi-urban settings. This strategy has the potential to be integrated into stunting prevention programs in primary healthcare, community health posts, and community-based interventions. Recommendation: Implementation should be accompanied by healthcare worker support and continuous monitoring to ensure sustainable behavior change